2020
DOI: 10.1039/d0sm00427h
|View full text |Cite
|
Sign up to set email alerts
|

Protonated state and synergistic role of Nd3+ doped barium cerate perovskite for the enhancement of ionic pathways in novel sulfonated polyethersulfone for H2/O2 fuel cells

Abstract: 1.8 times higher current density and power density were obtained for a Nd3+ doped barium cerate membrane compared to pure SPES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“… 41,43,44 The interfacial interplay of PAI and BaCeO 3 with SPEEK forming the hydrogen bond via polar groups and hinder the attack of free radicals in the HSO 3 groups. These restrictions made the minimal formation of radical in cathode sites and the benefit of BaCeO 3 nanoparticles favors the reduction reaction process 16,40,45 . The comparison of performance (B3) of the present study with Nafion and other membranes is shown in Table 3.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“… 41,43,44 The interfacial interplay of PAI and BaCeO 3 with SPEEK forming the hydrogen bond via polar groups and hinder the attack of free radicals in the HSO 3 groups. These restrictions made the minimal formation of radical in cathode sites and the benefit of BaCeO 3 nanoparticles favors the reduction reaction process 16,40,45 . The comparison of performance (B3) of the present study with Nafion and other membranes is shown in Table 3.…”
Section: Resultsmentioning
confidence: 91%
“…The protons are attached into the oxide lattice sites of BaCeO 3 via hydrogen bond under humid status. These are unbalanced and migrated to another oxide site only with adequate minimal potential 16,38‐40 . The octahedral (Ce‐O 4 ) arrangement was the favorable migration path for hopping and rotation process in perovskite material.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations